Emerging 2D metal oxides and their applications. (May 2021) - Kumbhakar, Partha; Chowde Gowda, Chinmayee; Mahapatra, Preeti Lata; Mukherjee, Madhubanti; Malviya, Kirtiman Deo; Chaker, Mohamed; Chandra, Amreesh; Lahiri, Basudev; Ajayan, P.M.; Jariwala, Deep; Singh, Abhishek; Tiwary, Chandra Sekhar
Graphical abstract: Abstract: In the past decade, several different classes of two-dimensional (2D) materials beyond graphene such as layered polymorphs of group V elements (phophorene, arsenene), Metalenes (gallenene, stanene etc.), Transition Metal–Dichalcogenides (TMDs), group III monochalcogenides, transition metal carbides as well as nitrides have been thoroughly explored. These atomically thin materials have gathered significant focus due to their unique electronic, optical, and magnetic properties, which are seldom found in their bulk counterparts due to the high surface to volume ratios and quantum confined electronic structure. These properties have led to excitement in the research community due to their potential applications in various fields of optoelectronics, energy harvesting and storage, sensing, electronics, magneto-electronics, and thermo-electronic applications. However, there is another emerging class of layered oxide 2D materials, which has been sporadically explored and lacks a systematic compilation of the made progress, potential benefits and research opportunities that may lie ahead. This specific review provides a thorough and systematic summary of research carried out on layered 2D oxides both from an experimental and theoretical perspective. Due to ultra-thin nature of the 2D metal oxides, a majority of the atoms are accessible to the surfaces, which induces new properties and applications in comparison to traditional bulk oxides. We discuss several different classes of metal oxides in their 2D forms such as MO, MO x, M x O y (where M stands for metals; x and y possible oxidation states) as well as Perovskite type oxides in this review specifically focusing on optoelectronics, sensing and electrochemical storage applications. We further make critical comparisons with bulk metal oxides, and elaborate the specific advantages of 2D metal oxides as compared to their bulk counterparts in respective applications. Finally, we conclude by providing a critical assessment and outlook of technical challenges and research opportunities for future development of layered 2D oxides.